Sistem Pendukung Keputusan Rekrutmen Jurnalis Baru Menggunakan Metode Simple Additive Weighting (SAW) Pada Jambi Independent - Lubis, Nia Paramitha; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2021)
Jambi Independent is the largest newspaper in the city of Jambi. One of the human resources in this Jambi Independent is a journalist. In selecting / selecting new journalist candidates, it takes a long time because it is not well systemized. The purpose of this study is to analyze and design a supporting system for the selection or recruitment of new journalist candidates at Jambi Independent by identifying their weaknesses and then analyzing the needs of the decision support system so that later it can help the personnel department and also to be considered in the selection of journalists.